Laryngomalacia: is there an evidence base for management?. Issue 11 (25th October 2017) - McCaffer, C; Blackmore, K; Flood, L M
Abstract: Background: The advent of supraglottoplasty clearly has transformed the surgical management of severe laryngomalacia. The condition, however, generally runs a milder course, with spontaneous resolution the norm. Objectives: To identify gaps in the knowledge and identify topics for future study. Method: Systematic review of the literature. Results: The literature suggests that there is a range of abnormalities leading to the typical collapsing upper airway, and that neurological disease, other airway abnormalities, syndromes and gastroesophageal reflux all contribute to disease severity and influence outcomes. The procedures involved in supraglottoplasty are rarely specified, the indications for surgery are vaguely defined and the role of medical therapy is unclear. Conclusion: Every review article or survey of opinion suggests that there is still a marked variation in individual practice and a lack of consensus.